Determinación de conocimientos técnicos y pedagógicos en economía doméstica de las extensionistas en Costa Rica - Bidigorri, H. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
A study was conducted to determine the level of technical and pedagogical knowledge of Extension agents of Costa Rica in certain aspects of home economics. The techniques used included direct observation, informal conversation and personal interviews with questionnaires. Among the conclusions arrived were: 1) the home demonstration agents have a higher image of their preparation than what they really have. 2) The level of knowledge was low. 3) They show more understanding in the areas that demand manual skills. Recommendations are made for future studies and for the improvement of the service.